Neoliberal capitalism, ASEAN integration and commodified education a Deluzian critique - Reyes, Raniel Sta. Maria (Budhi: a Journal of Ideas and Culture, 2015)
This article launches a Deleuzian critical diagnosis of neoliberal capitalism, which through the ASEAN Integration Project, expounds on capitalism’s effects on universities or on Philippine Higher Education. Strategists of neoliberal capitalism, whom Deleuze and Guattari call the “poor technician[s] of desire,” persuade underdeveloped or developing countries to see in their resources for financial stability or education reform, a “lack” that needs immediate attention and find solution in the global call for liberalization, deregulation, and privatization. Once this psychoanalytic ploy achieves success, these countries become naive preys of neoliberal capitalism. They interpret this phenomenon as a contemporary fascism that manipulates the people to desire increased order, unity, and their own repression. To counter this system, they formulate “schizoanalysis,” a radical philosophy that seeks the evisceration of psychoanalytic capitalism. In this article I use schizoanalysis or rhizomatic thinking to diagram a Deleuzian becomingrevolutionary in the sphere of education.